Effectivity of kiwi and sukamahi dam on jakarta flood control - Mardjono, Airlangga; Tri Juwon, Pitojo; Montarcih Limantara, Lily; Suhartan, Ery (International Journal of Engineering and Technology, 2018)
Various infrastructures such as flood levees, dams and reservoirs of flood control began to be developed in the 19th century to the 20th century. These buildings are very effective in controlling the flow of rivers and preventing flood waters from entering residential areas located in flood-prone areas. Flooding in urban areas has a huge impact, covering all aspects of life as well as on the landscape. Ciliwung is one of the rivers that allegedly contributed to the problem of flood in Jakarta, various engineering done on Ciliwung to help control flooding in Jakarta. One of the engineering done is the construction plan of Ciawi Reservoir and Sukamahi Reservoir. In this research, the writer performed the flood calculation using Nakayasu while method of flooding is calculated using the pool routine level method. The effectiveness of these two reservoirs can be determined by simulating floods in the existing condition and comparing them with the flood simulation after the construction of the dam. The final test of this research is to determine the effectiveness level of Ciawi and Sukamahi dam infrastructure in reducing flood volume in Jakarta.Â Â